Analisis Penerapan Psak 409 dalam Pelaporan Keuangan Zakat, Infak, dan Sedekah pada NU CARE–LAZISNU MWCNU Babat untuk Mewujudkan Akuntabilitas dan Transparansi - Nurul Alfiatun Nisa; Ahmad Fahrudin Alamsyah (Jurnal Riset Akuntansi, 2026)
The purpose of this study is to evaluate the implementation of PSAK 409 to achieve accountability and transparency in the financial reporting of zakat, infaq, and sedekah (ZIS) at NU CARE–LAZISNU MWCNU Babat. A qualitative approach utilizing case studies and descriptive analysis was the research methodology used. The Miles and Huberman methodology, which includes data reduction, data presentation, and conclusion drawing, was used to examine data collected through observation, interviews, and documentation. The findings indicate that ZIS LAZISNU MWCNU Babat's financial management and reporting procedures are still not fully compliant with PSAK 409. Complete financial reports, such as the statement of financial position, statement of changes in funds, cash flow statement, and notes to the financial statements, have not been published, and financial recording is still done simply and manually. This results in the institution's less-than-ideal accountability and transparency. Limited human resources, lack of knowledge of sharia accounting rules, and inadequate record-keeping systems are the main obstacles hindering the implementation of PSAK 409. Therefore, to create more accountable and transparent financial reports and increase public trust in zakat management institutions, efforts are needed to strengthen the record-keeping system, improve human resource competency, and support the implementation of PSAK 409.